Surveillance for Antibiogram Pattern of Nosocomial Bacteria from two Selected Hospitals in Kano State, Nigeria - Bale, S.I.; Mukhtar, M.D. (UMYU Journal of Microbiology Research)
In a bid to determine the level of antimicrobial resistance among bacterial pathogens feared to be nosocomially transmitted in some hospitals, Firstly, patients of HCAI was identified and followed-up accordingly with standardized questionnaire in the hospitals. Sample were collected for bacteriological assay using Culture and biochemical methods for the investigation of bacteria associated with nosocomial, Antibiogram pattern was assessed by Disk diffusion as to mark the resistant ones and presence of gene encoding for mecA and blaZ with the aid of PCR. At AKTH, A total of 63% of isolates were Gram-positive while 37% were Gram-negative bacteria. S. aureus were the most common isolates with frequency of 37%. Most of all the Gram-positive isolates were resistant to cefuroxime (30μg) and Amoxicillin (10μg) while they shown high sensitivity to other antibiotics tested against them. Only 18% of S. aureus are suspected MRSA. Most of Gram-negative isolates were found to be resistant to amoxicillin (10μg) 100%, gentamicin (10μg) 71% and chloramphenicol (30μg) 57%. At MMSH, 86% of the isolates were Gram-positive while 14% were Gram-negative bacteria. S. aureus, 42% were the most common isolates. All the isolates were resistance to cefuroxime and Amoxicillin (10μg) while they showed sensitivity to other tested antibiotics. while most shows sensitivity to other tested antibiotics. Only 24% of S. aureus were MRSA. 63% of the tested MRSA were mecA positive while 100% were blaZ positive. The high rates of resistome of isolates represent a substantial threat to the public where well-structured and continuous surveillance system for antimicrobial resistance is needed to encourage the monitoring of antimicrobial therapy.